Copper (II) lead (II), and zinc (II) reduce growth and zoospore release in four zoosporic true fungi from soils of NSW, Australia. Issue 7 (July 2015) - Henderson, Linda; Pilgaard, Bo; Gleason, Frank H.; Lilje, Osu
Abstract: This study examined the responses of a group of four zoosporic true fungi isolated from soils in NSW Australia, to concentrations of toxic metals in the laboratory that may be found in polluted soils. All isolates showed greatest sensitivity to Cu and least sensitivity to Pb. All isolates showed significant reduction in growth at 60 ppm (0.94 mmol m −3 ) for Cu, while three declined significantly at 60 ppm (0.92 mmol m −3 ) Zn. The growth of two isolates declined significantly at 100 ppm (0.48 mmol m −3 ) Pb and one at 200 ppm (0.96 mmol m −3 ) Pb. The rate of production of zoospores for all isolates was reduced when sporangia were grown in solid PYG media with 60 ppm Cu. Three isolates significantly declined in production at 60 ppm Zn and three at 100 ppm Pb. All isolates recovered growth after incubation in solid media with 60 ppm Zn or 100 ppm Pb. Two isolates did not recover growth after incubation in 60 ppm Cu. If these metals cause similar effects in the field, Cu, Pb, and Zn contamination of NSW soils is likely to reduce biomass of zoosporic true fungi. Loss of the fungi may reduce the rate of mineralisation of soil organic matter. Highlights: Copper, lead and zinc reduced the growth and reproduction of zoosporic true fungi. Isolates showed greatest sensitivity to Cu and least sensitivity to Pb. All isolates recovered growth after incubation with Pb and Zn but not Cu.